Knowledge and Awareness of Medical Students for Protective Measures against COVID-19 (Medical Forum Monthly, 2022)
Objective: Our study aimed to assess the knowledge and awareness of medical students for preventive and protective measures towards Covid-19.Study Design: descriptive observational cross sectional studyPlace and Duration of Study: This study was conducted at the institutes of southern Punjab including Nishtar Medical University, Multan, Bakhtawer Amin Medical College, Multan and Quade Azam Medical College, Bahawalpur from June, 2020 to September, 2020.Materials and Methods: A structured questionnaire based on demographic, COVID -19 related information and practice for preventive measures was distributed online among medical students of southern Punjab, Pakistan. The response of students was recorded and result was analyzed.Results: Out of 736 students 287 (39%) were males and 449 (61%) were females. Over all 85% students showed appreciable awareness for predisposing factors, virology, preventive and protective measures Clinical students were more aware as compare to pre-clinical students. Awareness was better among male students as compare to females one. The most common source of gaining knowledge was social media. Clinical students were in good practice of preventive and protective measures. Direct dealing or contact with Corona patients in wards might be the cardinal reason for good awareness and preventive practice in clinical students. Observation of the intensive treatment required for symptomatic patients and poor outcome in some patients is another fundamental ground that increases the Covid fear or anxiety and the thirst for gaining more information and knowledge.Conclusion: Medical students are asset of a nation, being the future frontline worriers against these kinds of pandemics. Overall, the Covid Related knowledge was deficit among pre-clinical and female medical students. Awareness for covid-19 pandemic is the one and only key to protect our medical students and its associated mental and physical impact but unfortunately is an ignored aspect in developing countries. There is need of intervention by public health department for designing awareness and education plans.